MANAJEMEN LAPORAN PENGADUAN PELAYANAN PUBLIK OLEH OMBUDSMAN PERWAKILAN PROVINSI RIAU DI KOTA PEKANBARU - Weri Syaputra; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The research present describe management report of public services by Ombudsman Republic of Indonesia district Riau Province subdistrict Pekanbaru City. One of main job describtion a government are public services as a democracy state. Since reformation era Indonesia government always do instropections for their authority, but until now still report from the society about the problem of public service. In order that since 2002 Indonesia government create a institutions that have function to receive and investigation the report from the society are Ombudsman Republic of Indonesia. Until now Ombudsman have a representative in every Province in Indonesia and can make optimalization their function.The research use the methode are qualitative methodes that analyze problem research by describe the subject and object conditions based on real fact. This research use location in Pekanbaru City and researcher collect data from books, government regulation, jurnal, mass media, website and deep interview with informan likes Head of Ombudsman Representative of Riau Province, Commisioner of Ombudsman Representative of Riau Province and the citizens that has report.The conclusion of this research about management report of public services by Ombudsman Republic of Indonesia district Riau Province subdistrict Pekanbaru City are done by some steps likes receive and registration a report from society and inisiative from Ombudsman, processing a report and investigations a report from society by mediation, special adjudication and systemic review and output from Ombudsman by result and recomendation and publication report for precident, legislative and mass media. Some factors that cause the management report of public services by Ombudsman Republic of Indonesia district Riau Province subdistrict Pekanbaru City are minims of human resources in Ombudsman Representative of Riau Province, minims of budgeting and facility in Ombudsman Representative of Riau Province.Keywords: management, report, society and Ombudsman.